DATA SCIENCE FOR BUSINESS - PROVOST FOSTER; TOM FAWCET (O'REILLY MEDIA INC CA California`, 2013)
The book "Data Science for Business" by Foster Provost and Tom Fawcett is a comprehensive guide to understanding data science principles and their practical application in business contexts. It emphasizes the importance of data-analytic thinking as a structured approach to solving business problems using data. The authors stress the significance of predictive modeling, data mining, and model evaluation techniques like cross-validation to ensure reliable data-driven decisions.
Data Science for Business
Data Science & Management
BBA & CSE & MBA
Keywords: DATA SCIENCE; BUSINESS; MANAGEMENT